Innovative Multi-Color LED HPL Lamps for Improved Efficiency in Floating Lift Net Fishing - Jailani, Abdul Qadir; Suharyanto, Suharyanto; Ruchimat, Toni (Grimsa Journal of Science Engineering and Technology, 2025)
This research focuses on the design and fabrication of a high-power LED (HPL) light that integrates red, green, and blue LEDs for underwater lighting, commonly known as "lacuda," used on floating fishing rafts. The lamp features an aluminum heatsink with integrated fins for efficient heat dissipation and is coated with a resin-catalyst mixture for durability. The study involved measuring, drafting, assembling, and wiring the LEDs, followed by field testing in Krueng Raya Bay, Aceh Province. The primary objective was to evaluate the performance of HPL LED lights compared to traditional tubular fluorescent lamps (TL) used on floating rafts. Results showed that the HPL LED lights met design specifications and were technically suitable for fishing operations. Notably, they proved more efficient than TLs by providing superior light penetration when submerged, addressing the limitations of surface-mounted lighting. These findings suggest that HPL LED lights are a viable alternative for underwater lighting in fishing operations.